Aplikasi Model Pembelajaran Sinektik (Synectic Model) - Karwati, Uus - (PANGGUNG, 2012)
ABSTRACTÃÂ The title of this article is Application of Synectic Learning Model in Kampung Seni & Wisata Manglayang, Bandung regency. This paper is motivated by the idea of conceptualization necessities of learning in art studios which provide learning services to the visitors, especially of the early ages. The research used a qualitative paradigm with pseudo experiment approach of one short case study applying Synectic Learning Model that is an approach to develop creativity, to enhance problem- solving skills, creative expression, and to develop empathy in social relationships. Through its ap- plication the art learning activities in the studio visitation program is more meaningful and able to develop ideas and enhance creative activities of the students.ÃÂ Keywords: Synectic Learning Model.